Influence of Internal and External Auditors Attribution on Quality Audit with Moderating Auditor Ethics at Public Accounting Office in Surabaya - Aan Nurrohman; Tarjo; Agus Sumanto (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This research was conducted test whether attributions internal and external auditors include: independence, competence, experience and time budget pressure affect quality audit at Surabaya Public Accounting Firm (KAP) moderated by auditor ethics. The research sample includes some auditors at KAP Surabaya many 58 people. The sampling technique in the research uses purposive sampling. Data analysis and testing was carried out using moderating regression, which was processed using the SPSS version 22 application. Hypothesis testing was carried out using the t test and F test. The test results prove that independence, time budget pressure, and competence have influence positive and significant in audit quality, and experience does not affect quality audit. Effect of experience, competence, and time budget pressure in quality audit is moderated auditor ethics. The relationship between independent variables in quality audit not moderated with auditor ethics. Keywords: competence, independence, experience, time budget pressure, audit quality and auditor ethics.